Forensic Assistance Project: Consultant Report 1999-051 Livno Cave I Republika Srpska Commission on Tracing Prisoners and Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Drayer, Francine On September 3 and 4, 1999, the Republika Srpska Commission on Tracing Prisoners and Missing Persons recovered an as yet undetermined number of human remains from a karst pit near Livno. The cave is located just north of Livno on a hill overlooking the city. The minimum number of individuals (MNI) is not known because no reconstruction of bodies was attempted during recovery, due to the hazardous and difficult conditions. All individuals appeared to be those of adult males. Place of Exhumation: Livno cave Date of Exhumation: 3-4 September 1999